ANALYTICAL STUDY ON NASR HAMID ABU ZAYD’S UNDERSTANDING OF RELIGIOUS TEXTS IN ISLAM - Falyouna, Nader A. M. (Journal of Al-Tamaddun, 2020)
Understanding religious texts in Islam has differed since the time of the Prophet Mohammed. After this era, two schools with different concepts were formed to handle religious texts: a school that commits to the orignal text literally regardless of contextual considerations, and another places the importance of having a reference to other contextual determinants. Thus, the jurists continued to understand the texts through what was established by the scholars of the two schools. Later, a group of scholars tried to develop a new approach to understand the texts based on non-adherence to the former curricula. They believed that Muslims were impacted by events that took place in their social life, the way they understood Islam, and the political situation that surrounded them. It was necessary to develop a new approach to meet the demands of the developments of the era, serving as a mean to get out of the decline of Muslims in light of the modern European Renaissance. The most prominent of these thinkers was Nasr Abu Zayd, who has caused a stir in public and intellectual circles in Egypt. This research paper sheds light on a range of political factors that influenced the formation of his thoughts.